2003
DOI: 10.1002/clc.4960261207
|View full text |Cite
|
Sign up to set email alerts
|

Association of aortic valve sclerosis and coronary artery disease in patients with severe nonischemic mitral regurgitation

Abstract: Background: The presence of aortic valve sclerosis accounts for a higher rate of ischemic events and increased cardiovascular mortality. It may reflect coronary artery disease (CAD) because of a shared pathologic background. Hypothesis: We aimed to analyze whether the presence of aortic valve sclerosis might help in identifying patients with coronary atherosclerosis among those with severe nonischemic mitral regurgitation (MR), who undergo coronary angiography before surgery for screening, and not because of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It is known that there are similarities in the histopathologic lesions of AVS, MAC, and coronary atherosclerosis and that these three diseases share multiple CVD risk factors (e.g., hypertension, smoking, dyslipidemia, and diabetes) and common pathophysiologic mechanisms ( 1 3 , 18 , 21 ). More recent studies suggested that AVS and MAC are not only associated with coronary atherosclerosis but also with atherosclerosis in other vascular beds ( 21 25 ). However, since in our study the HVC score strongly predicted CVD mortality independently of traditional CVD risk factors and other potential confounders, it is also possible to speculate that AVS and MAC, singly or in combination, reflect not only the burden of systemic atherosclerosis ( 1 3 , 21 , 26 , 27 ) but also the presence of other underlying conditions, which may predispose patients to active and accelerated atherosclerosis, such as systemic chronic inflammation ( 21 , 28 ), platelet aggregation abnormalities ( 21 , 29 ), and genetic predisposition ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that there are similarities in the histopathologic lesions of AVS, MAC, and coronary atherosclerosis and that these three diseases share multiple CVD risk factors (e.g., hypertension, smoking, dyslipidemia, and diabetes) and common pathophysiologic mechanisms ( 1 3 , 18 , 21 ). More recent studies suggested that AVS and MAC are not only associated with coronary atherosclerosis but also with atherosclerosis in other vascular beds ( 21 25 ). However, since in our study the HVC score strongly predicted CVD mortality independently of traditional CVD risk factors and other potential confounders, it is also possible to speculate that AVS and MAC, singly or in combination, reflect not only the burden of systemic atherosclerosis ( 1 3 , 21 , 26 , 27 ) but also the presence of other underlying conditions, which may predispose patients to active and accelerated atherosclerosis, such as systemic chronic inflammation ( 21 , 28 ), platelet aggregation abnormalities ( 21 , 29 ), and genetic predisposition ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Literature data on the association of aortic valve sclerosis with coronary artery disease or coronary ischemic events are controversial, ranging from reports suggesting a 50% increase in cardiovascular mortality to those demonstrating an association with coronary artery disease to recommendations for secondary prevention with statins or angiotensin-converting enzymes in AVS patients [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] . At the other extreme, Chandra and colleagues found no association between aortic valve sclerosis and the all-cause or cardiovascular mortality endpoint 48 , and Tolstrup et al found no association between aortic valve sclerosis and coronary artery disease 49 .…”
Section: Discussionmentioning
confidence: 99%